2013
DOI: 10.1016/j.jspi.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting probabilistic scoring rules

Abstract: There are several scoring rules that one can choose from in order to score probabilistic forecasting models or estimate model parameters. Whilst it is generally agreed that proper scoring rules are preferable, there is no clear criterion for preferring one proper scoring rule above another. This manuscript compares and contrasts some commonly used proper scoring rules and provides guidance on scoring rule selection. In particular, it is shown that the logarithmic scoring rule prefers erring with more uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Equivalently, the associated divergence or discrepancy function (Dawid, 1998), given by D.P; Q/ WD S.P; Q/ S.P; P /, is always non-negative. There is a very wide variety of proper scoring rules: for general characterizations see, among others, McCarthy (1956) and Savage (1971), and for various special cases, see Dawid (1998Dawid ( , 2007, Dawid & Musio (2014), Gneiting & Raftery (2007) and Machete (2013). We now consider some of these in more detail.…”
Section: Proper Scoring Rulesmentioning
confidence: 99%
“…Equivalently, the associated divergence or discrepancy function (Dawid, 1998), given by D.P; Q/ WD S.P; Q/ S.P; P /, is always non-negative. There is a very wide variety of proper scoring rules: for general characterizations see, among others, McCarthy (1956) and Savage (1971), and for various special cases, see Dawid (1998Dawid ( , 2007, Dawid & Musio (2014), Gneiting & Raftery (2007) and Machete (2013). We now consider some of these in more detail.…”
Section: Proper Scoring Rulesmentioning
confidence: 99%
“…Quoting the authors: "it is insufficient to use a scoring rule simply because it is strictly proper; instead, it is beneficial to consider the specific way in which the scoring rule rewards and penalizes forecasts" (Merkle and Steyvers 2013, p. 302; emphasis added). Machete (2013) also suggested that the proper scoring rule one chooses should depend on the application at hand, and an issue to consider may be future decisions associated with high impact, low probability events. In particular, given two forecasts whose errors from the ideal distribution differ only by the sign, Machete (2013) found that the logarithmic scoring rule scores higher the forecast with the highest entropy, the spherical scoring rule scores higher the forecast with the lowest entropy, and the quadratic scoring rule does not distinguish between the two forecasts.…”
Section: Choosing a Proper Scoring Rulementioning
confidence: 99%
“…Machete (2013) also suggested that the proper scoring rule one chooses should depend on the application at hand, and an issue to consider may be future decisions associated with high impact, low probability events. In particular, given two forecasts whose errors from the ideal distribution differ only by the sign, Machete (2013) found that the logarithmic scoring rule scores higher the forecast with the highest entropy, the spherical scoring rule scores higher the forecast with the lowest entropy, and the quadratic scoring rule does not distinguish between the two forecasts. In other words, the logarithmic (respectively, spherical) scoring rule should be used when more (respectively, less) uncertainty is desirable.…”
Section: Choosing a Proper Scoring Rulementioning
confidence: 99%
“…To deal with complex models or model misspecifications, useful surrogate likelihoods can be obtained trough proper scoring rules. A scoring rule (see, for instance, the recent overviews by Machete, 2013, andMusio, 2014, and references therein) is a special kind of loss function designed to measure the quality of a probability distribution for a random variable, given its observed value. It is proper if it encourages honesty in the probability evaluation.…”
Section: Introductionmentioning
confidence: 99%